2016
DOI: 10.1590/1981-863720160001000072929
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness of a resin composite

Abstract: ObjectiveThe aim of the present study was to evaluate the surface roughness (Ra) of the Z-350 resin composite following immersion in different media (distilled water, coca-cola, coffee, black tea and red wine). Methods Fifty Results A significant increase in Ra was found in the specimens submitted to coffee, coca-cola ® and black tea between baseline and the three-month evaluation. Variance was also found among the remaining evaluation times (3 months to 12 months), but the differences did not achieve statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The exposure to coffee increased the resin surface roughness and stain- ing if compared to control group, independently of the association to SBAP. This fact can be due to coffee's acid pH, around 5.0, as well as the presence of long-chain organic acids, that they can promote dissolution and corrosion on restorative materials 6 .It is reported that the coffee also has high temperature, as used in this experiment, that it can promote degradation of the resin matrix, since areas of material exposed to high temperatures exhibited considerable increased of roughness and superficial staining 27 .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The exposure to coffee increased the resin surface roughness and stain- ing if compared to control group, independently of the association to SBAP. This fact can be due to coffee's acid pH, around 5.0, as well as the presence of long-chain organic acids, that they can promote dissolution and corrosion on restorative materials 6 .It is reported that the coffee also has high temperature, as used in this experiment, that it can promote degradation of the resin matrix, since areas of material exposed to high temperatures exhibited considerable increased of roughness and superficial staining 27 .…”
Section: Discussionmentioning
confidence: 78%
“…Overall, the surface quality of the restorative material influences the clinical performance and durability of restorations 5 , since the maintenance of flat surface decreases early alterations of color and shine, besides of reducing the biofilm growth on surface restoration, which decreases risk of secondary caries lesions and periodontal inflammation [4][5][6][7][8][9] . The roughness present on resin surface can be detected by the tip of the patient's tongue since 0.3µm 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite bars with approximately 2×2×12 mm dimensions were used for surface roughness assessments before starting the ion release and recharge. The average surface roughness (R a, μm) was measured with a Mitutoyo (SJ-310 SURFTEST, Kanagawa, Japan) surface roughness tester following a previous study (n=6) 37) . In a previous study, composite surfaces produced using Mylar strips showed surface roughness values that were not significantly different from the Enhance/BisCover finishing protocol 38) .…”
Section: Composite Surface Roughnessmentioning
confidence: 99%